Vitamin D status in children with attention‐deficit–hyperactivity disorder. Issue 4 (17th June 2014) - Goksugur, Sevil Bilir; Tufan, Ali Evren; Semiz, Murat; Gunes, Cemalettin; Bekdas, Mervan; Tosun, Mehmet; Demircioglu, Fatih
Abstract Background Attention‐deficit–hyperactivity disorder (ADHD), one of the most common psychiatric disorders of childhood, has an early onset, affecting 2–18% of children worldwide. The etiopathogenesis of ADHD is obscure. In recent studies, a low level of vitamin D has been found in association with many disorders as well as in neuropsychiatric diseases. The aim of this study was therefore to investigate serum vitamin D level in pediatric ADHD patients. Methods A total of 60 ADHD patients and 30 healthy controls were included in the study. The age of both groups was in the 7–18‐year‐old range. Serum 25‐OH‐vitamin D, calcium, phosphorus and alkaline phosphatase were investigated. Results Serum 25‐OH‐vitamin D was found to be significantly lower in children and adolescents with ADHD compared to healthy controls, and no significant differences were found between the groups in terms of other variables. 25‐OH‐vitamin D level in the ADHD group and control group was, respectively, 20.9 ± 19.4 ng/mL and 34.9 ± 15.4 ng/mL (P = 0.001). Conclusion There is an association between lower 25‐OH‐vitamin D concentration and ADHD in childhood and adolescence. To the authors' knowledge this is the first study to investigate the relationship between vitamin D and ADHD in children.